2008
DOI: 10.1210/en.2008-0749
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidic Acid Signaling during Embryo Development in Sheep: Involvement in Prostaglandin Synthesis

Abstract: We investigated the lysophosphatidic acid (LPA) pathway during early pregnancy in sheep. LPA was detected in the uteri of early-stage pregnant ewes. Using quantitative RT-PCR, the expression of autotaxin, the LPA-generating enzyme, was found in the endometrium and conceptus. In the latter autotaxin, transcript levels were low on d 12-14 and increased on d 15-16, in parallel with the level of LPA. Autotaxin was localized in the luminal epithelium and superficial glands of the endometrium and in trophectoderm ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
71
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 83 publications
8
71
1
Order By: Relevance
“…Indeed, in mouse, sheep, pig and human, LPA 3 was expressed in the uterine epithelial layer in a female sex hormone‐dependent manner (Hama et al , 2006; KamiƄska et al , 2008; Liszewska et al , 2012; Guo et al , 2013). In addition, ATX and LPA were detected in the reproductive biological fluids such as follicular fluids and uterine luminal fluids (Liszewska et al , 2009; Seo et al , 2012; Yamamoto et al , 2016). Thus, LPA 3 appears to regulate the female reproductive systems in wide range of mammalian species including human, although there are some slight differences in the process of decidualization between species (Cha et al , 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in mouse, sheep, pig and human, LPA 3 was expressed in the uterine epithelial layer in a female sex hormone‐dependent manner (Hama et al , 2006; KamiƄska et al , 2008; Liszewska et al , 2012; Guo et al , 2013). In addition, ATX and LPA were detected in the reproductive biological fluids such as follicular fluids and uterine luminal fluids (Liszewska et al , 2009; Seo et al , 2012; Yamamoto et al , 2016). Thus, LPA 3 appears to regulate the female reproductive systems in wide range of mammalian species including human, although there are some slight differences in the process of decidualization between species (Cha et al , 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, LPA stimulates progesterone (P4) and prostaglandin (PG) E2 secretion in vivo, and its receptor gene expression (LPA1) is positively correlated with expression of the enzyme responsible for luteotropic PGE2 production (PGES) in the bovine endometrium during the estrous cycle and early pregnancy. These data indicate that LPA may play autocrine and/or paracine roles in the uterus and serve as an important factor in maintenance of early pregnancy not only in the mouse [9], pig [10,11] and sheep [12], but also in the cow [13].…”
mentioning
confidence: 83%
“…Moreover, LPA stimulates progesterone (P4) and prostaglandin (PG) E2 secretion in vivo, and its receptor gene expression (LPA1) is positively correlated with expression of the enzyme responsible for luteotropic PGE2 production (PGES) in the bovine endometrium during the estrous cycle and early pregnancy. These data indicate that LPA may play autocrine and/or paracine roles in the uterus and serve as an important factor in maintenance of early pregnancy not only in the mouse [9], pig [10,11] and sheep [12], but also in the cow [13].In ruminants, like in many other mammals, establishment of pregnancy involves maternal recognition of pregnancy and implantation. There is much evidence showing that the maternal recognition of pregnancy in ruminants requires that the conceptus elongate from a spherical to tubular and then filamentous form to produce interferon tau (IFNτ), which is the pregnancy recognition signal that prevents development of the endometrial luteolytic mechanism [14,15].…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…56: [411][412][413][414][415][416][417][418][419][420] 2010) he role of lysophosphatidic acid (LPA) in the reproductive system has been studied extensively in mice [1], pigs [2,3], ewes [4] and cows [5][6][7]. We found that in the bovine endometrium, in contrast to the mouse, pig and sheep [1][2][3][4], there is mRNA expression only for the LPA receptor type 1 (LPAR1) [5]. We also demonstrated that LPA is locally produced and released from the bovine endometrium [5].…”
mentioning
confidence: 99%